(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Oral health decline among institutionalised older adults is closely linked to caregiver-dependent hygiene practices and reflects the effectiveness of internal care management systems. This study examined the impact of structured oral care education management embedded within institutional policies, including standard operating procedures, supervision, and routine documentation, on caregiver performance and resident oral health outcomes. An explanatory sequential mixed-method design was conducted in a long-term care facility involving 40 caregivers and 72 older adults. A four-week structured education programme integrated with supervisory reinforcement and documentation protocols was implemented as part of routine care governance. Caregiver adherence to the complete oral care sequence increased from 61% to 89%, while omission frequency decreased from 29% to 7%. Mean plaque index declined from 2.8 to 1.4, heavy plaque presence from 36% to 8%, and mucosal irritation from 42% to 14%. Chewing confidence improved in 67% of residents. Improvements were sustained through the final observation period. These findings demonstrate that oral care education functions most effectively when institutionalised through internal policies, reinforcing its role as a management-driven strategy to sustain caregiver performance, oral comfort, and quality of life in long-term care settings.